The Mechanisms of CellularImmune Response in Brucellosis - V. I. Dubrovina; Zh. A. Konovalova; K. U. Yastremskaya; N. L. Barannikova; L. E. Tokareva; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2016)
The current state of the problem of Brucella interactions with the host in the review is discussesed. Provides information about the mechanisms of persistence of Brucella in the host organism due to their ability long remain in the cells immunoregulatory system. Data on the differences of Brucella in smooth and rough forms on invasive ability are presented. The key role of the macrophage in Brucella infection is shown. Promising areas of research in the field of immunobiology of brucellosis are indicated.